Integrated volatile metabolome and transcriptome analyses provide insights into the warm aroma formation elicited by methyl jasmonate in carrot root - Wang, Guang-Long; Wu, Jia-Qi; Chen, Yang-Yang; Xu, Yu-Jie; An, Ya-Hong; Ren, Xu-Qin; Xiong, Ai-Sheng (Frontiers in Plant Science, 2024)
Carrot is a highly significant vegetable cultivated worldwide and possesses a unique aroma with abundant edible and medicinal values. However, it remains largely unknown whether jasmonic acid could regulate aroma formation in carrot. Here, an integrated analysis of the volatile metabolome and transcriptome of carrot roots exposed to different concentrations of methyl jasmonate (MeJA) was performed. The results revealed 1,227 volatile organic compounds and 972 differential accumulated metabolites, with terpenes representing the largest portion. MeJA treatment evidently increased the relative odor activity values as well as the accumulation of most volatile compounds. In addition, 4,787 differentially expressed genes were identified and subjected to function enrichment analysis, indicating a role of terpene biosynthesis and metabolism in response to MeJA application. A network consisting of 4,680 transcription factor-structural pairs that showed highly significant positive correlations was constructed, which may be utilized as genetic targets for examining terpene accumulation and aroma formation elicited by methyl jasmonate. The results from the present work substantially improved our understanding of MeJA-mediated aroma formation in carrot.